Interconnection of Prime Service on Organization's Public Sector: A Study on Department of Demography and Civil Record of Manado City's Government North Sulawesi Province - Pangkey, Itje; H.E Sendouw, Recky (International Journal of Psychosocial Rehabilitation, 2020)
The aim of this research was to analyze public service in the Department of Demography and Civil Records of Manado City's Government and Childbirth Service in the General Hospital of Prof. Dr. Kandouw. Method: research, qualitative method of approach case studies, researcher went directly into the field in collecting the data by asking along with interview the people concerning the service of government institute to the public in Department of Demography and Civil Record in the document service of birth certificate in Manado City and doing interview to medic in childbirth section and mother or family who did childbirth. The data collection technique, the in-depth interview technique, was done by logical questions based on the guidance statement and exact target by not evoking suspicion from the informant. The interview was done by getting strong intimacy. The researcher kept following what Benny and Hughes said about appreciating the value of the interview as a tool of data collection. Data Analysis Technique: qualitative data analysis, with procedure, data reduction, and data presentation. The results that have been achieved on the arrangement of the birth certificate, the obscurity of the officer to give the document, and the high (relative) fee for making the document must go back and forth to the hospital to get the birth reference as the requirement for the birth certificate, but the employees are not responsive to society. After analyzing the problem to increase community satisfaction index and read the theory alone with experts’ study, researcher found out SPT Dukun 3 in 1 Model (Integrated Service System of Childbirth Document and Population).